Closing the middle-skills gap widened by digitalization: how technical universities can contribute through Challenge-Based Learning. Issue 8 (3rd August 2022) - Colombari, Ruggero; Neirotti, Paolo
ABSTRACT: The digitalization of operations is disrupting frontline technical jobs, entailing new competency needs currently not being met by upper secondary education and corporate training programs. To discuss how technical universities can help bridge the resulting "middle-skills gap" without incurring an unwarranted academization of these professions, a two-cycle participatory action research was conducted within the empirical setting of a leading Italian electric-power distribution company. First, an in-depth case study investigated how the advent of smart grids is transforming the work of frontline operation and maintenance workers. Second, a Challenge-Based-Learning intervention was co-designed according to the emerging competency gaps, and tested with two classes involved in the company's school-based apprenticeship program. The findings contribute to literatures on knowledge creation and transformation by academics, and on developmental universities, respectively: technical universities can design effective challenge-based programs thanks to state-of-the-art laboratories, multidisciplinary research, diverse teaching domains, and a stimulating environment; moreover, they can transfer these innovative research-based teaching methods and restore the socio-economic attractiveness of technical schools and professions, thus playing a developmental role in the middle-skills gap issue. A major policy implication that emerges is the – rather urgent – need to foster initiatives aimed at a deeper integration between upper secondary and higher education systems.